Comparative evaluation of thyroid imaging reporting and data system and cytopathological correlation in thyroid nodules - Muthanna BA,; Satyendra Raghuwanshi,; Sanjay Kumar,; Mathur, Yashvir; Nalin Singh,; Rohit Aggarwal, (Asian Journal of Medical Sciences, 2023)
Background: With the increasing availability of ultrasound (USG) and concern for malignancy, there has been significant increase in the detection of thyroid lesions. However, there is no uniformity in the reporting pattern among radiologists, and hence, such USG reports are mostly inconclusive to exclude thyroid malignancy. Therefore, most of the patients have to undergo fine needle aspiration cytology or fine needle non-aspiration cytology (FNNAC), which is avoidable. The sonographic assessment of thyroid nodule can provide alternative method to this invasive modality of diagnosis. Therefore, the need was felt for establishing uniformity in USG reporting of thyroid nodules and risk stratification for malignancy with aim of reducing unnecessary FNNAC. Thyroid imaging reporting and data system (TIRADS) classification brings uniformity in reporting and reduces ambiguity in management of the patients. Aims and Objectives: The objective of the study was to perform comparative evaluation of TIRADS and cytopathological evaluation of thyroid nodules FNNAC in Indian scenario. Materials and Methods: Multicentric prospective study was conducted in the department of radio diagnosis and department of surgery at defence service hospitals of Jaipur and Chandimandir during the study period of July 01, 2017–October 31, 2022. Results: Out of the 208 nodules, 28 (13.5%) turned out to be malignant. The percentage of malignant thyroid nodules was higher in nodules with TIRADS scores 4 and 5. The percentage of malignant thyroid nodules was 1% and 2%, respectively, for TIRADS 2 and 3 categories. The most common finding of USG evaluation was diffuse thyroiditis. There was a significant correlation between the USG findings and FNNAC findings in TIRADS scoring system. Conclusion: Our study shows high degree of correlation between TIRADS classification and cytopathological evaluation of thyroid nodules. Hence, TIRADS can be used an effective tool for avoiding unnecessary FNNAC procedures.